SITE DISTRIBUTION OF FE2+ AND FE3+ IN THE AXINITE MINERAL GROUP: NEW CRYSTAL-CHEMICAL FORMULA - Andreozzi G.B.; Lucchesi S.; Graziani G.; Russo U. (My University, 2004)
A set of nine samples of axinite, selected from 60 specimens from worldwide localities, were investigated by single-crystal X-ray diffraction, electron and ion microprobe, and 57Fe Mössbauer spectroscopy. The selected samples cover the compositional join from almost pure ferroaxinite (80%) to pure manganaxinite (95%). A new crystal-chemical formula for the axinite mineral group is proposed: VI[X1 X2 Y Z1 Z2]2IV[T1 T2 T3 T4 T5]2O30(OwOH1-w)2, where VI and IV are coordination numbers; X1 = Ca and very minor Na; X2 = Ca (in axinites) or Mn (in tinzenite); Y = Mn (in manganaxinite and tinzenite), Fe2+ (in ferroaxinite) or Mg (in magnesioaxinite), with minor Al and Fe3+; Z1 = Al and Fe3+; Z2 = Al; T1, T2, and T3 = Si; T4 = Si (and presumably very minor B); T5 = B and minor Si. Charge unbalance (w), due to heterovalent substitutions, is compensated for by O2- → OH- substitution. From ferroaxinite to manganaxinite, cell volume increases linearly from 568.70 to 573.60 Å3. This is mainly due to an increase in the mean distance from 2.220 to 2.255 Å, which is directly related to the Mn population (up to 1.89 apfu). Fe3+ concentrations, as determined by 57Fe Mössbauer spectra at 80 K, sub-regularly increase up to 0.27 apfu, and three cases are evidenced: (1) Fe3+ << Fe2+ (or no Fe3+), in ferroaxinite; (2) Fe3+ < Fe2+, in intermediate compositions, and (3) Fe3+ > Fe2+ (or only Fe3+), in manganaxinite. Chemical and structural data were co-processed via a computer minimization program to obtain the cation distribution scheme. Adopting the Hard-Sphere Model, empirical cation-oxygen distances were refined for every cation in the axinite structure. The results revealed that Fe2+ is ordered at the octahedral Y site (up to 1.61 apfu), whereas Fe3+ is ordered at the octahedral Z1 site (up to 0.26 apfu) and is almost absent in the smallest Z2 site, which is fully populated by Al. The observed Fe3+ partitioning is in agreement with the structural results, which show that the Z1 octahedron is always larger than Z2. Moreover, no Fe3+ is found at the tetrahedral sites, but Si → B substitution occurs at T5. The continuous Y dimensional increase from ferroaxinite to manganaxinite involves progressive enlargement of the edge-sharing Z1 octahedron. As a consequence, the Z1Fe3+ → Z1Al3+ substitution is structurally favored toward manganaxinite and points to a new end-member with the suggested name “ferri-manganaxinite.”
Keywords: axinite